Keselarasan Nilai Pancasila dengan Nilai Pendidikan Agama Kristen - Lena Natalia; Hendrik A. E. Lao; Andrian Wirasyahputra (Jurnal Pendidikan Agama dan Teologi, 2024)
Pancasila is the ideology of the Indonesian nation which functions as a foundation for acting, having a perspective and living in the Indonesian nation and state. The Pancasila principles contain important values ​​that must become the foundation and formation of national character; This is in accordance with the ideals of education in Indonesia, namely forming Pancasila Indonesian people. Pancasila values ​​should also be taught in every learning activity, including when teaching Christian Religious Education to students. The aim of this scientific work is to discuss the implementation of Pancasila values ​​in Christian Religious Education. This research uses a library study paradigm, where data collection efforts use various scientific literature. The data was analyzed descriptively to reveal the results that as Christians, every student must realize that as Indonesian citizens who are synonymous with diversity, they must live in unity and harmony based on the values ​​of Pancasila. Christians must see the harmony between Indonesian citizens that has existed for so long as a gift from God that must be maintained and preserved. The spirit of behaving in accordance with the values ​​of Pancasila is in harmony with the values ​​in Christian Religious Education learning, namely encouraging students in schools to be open and willing to appreciate the diversity of existing religions, respect human values, work together to maintain unity, respect the government and representatives, and apply fair wherever you are. Living the values ​​of Pancasila through teaching Christian Religious Education helps students experience character strengthening to behave positively as part of peace-loving Indonesian society.